Be ready when you're off duty to respond to an active shooter incident. Issue 6 (17th September 2018) - Hope, Joan
Abstract : FAIRFAX, Va. — Are you mentally and physically ready to address an active shooter situation — even if it occurs while you're not at work? Michael Howell, an officer with the Kansas City, Kansas, Police Department was shopping at Costco on his day off when an armed gunman threatened to shoot shoppers.